Subtyping of Properdin Factor B (Bf) by Isoelectrofocusing - Teng, Y.-S.; Tan, S.G. (Karger Publishers, 1982)
Properdin factor B (Bf) is a polymorphic protein in the human plasma. Two common alleles, BfS, BfF, and two rare alleles, BfF1, BfS1, have been demonstrated in Caucasians. We now report that BfF can be subtyped into two alleles, BfFa and BfFb by isoelectrofocusing. Family studies indicate that they are inherited in a co-dominant pattern. Gene frequencies for Caucasians are: BfS 0.808, BfF1 0.019, Bfs1 0.005, Bfs1 0.038 and BfFa 0.128.